Daddy's gone a hunting [compact disc, unabridged] - Clark, Mary Higgins (Simon & Schuster Audio, 2013)
A dark secret from a family's past threatens the lives of two sisters, Kate and Hannah Connelly. When the family-owned furniture firm, including the mansion where priceless antiques are kept, explodes into flames in the middle of the night, Kate must escape to save her life. But the suspicious circumstances point to her involvement.